Leishmaniasis - Jorge R. Rey (EDIS)
ENY-738, a 5-page illustrated fact sheet by Jorge R. Rey, describes this disease caused by parasitic protozoans transmitted to humans by sandflies. Includes description of the parasite, forms and symptoms, distribution, treatment, coinfection with HIV/AIDS, and references. Published by the UF Department of Entomology and Nematology, February 2007.